Marriage Contract in the Presence of a Corpse: Legal Perspectives in Islamic and State Law - Sari, Elsa Jeni Isma; Baihaqi, Yusuf; Hermanto, Agus (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
The tradition of conducting a marriage contract in front of the deceased parents’ bodies remains preserved in Aji Jaya KNPI Village, Gedung Aji District, Tulang Bawang Regency. Rooted in symbolic and spiritual motives—such as fulfilling the final wishes of the deceased and upholding family honor—this practice continues to be observed as a customary norm. This study aims to examine the validity of the practice from the perspective of Islamic law, assess its status through the concept of ʿurf ṣaḥīḥ, analyze the 40-day post-marital abstinence as a local customary prohibition, and construct normative arguments within the frameworks of Islamic family law and Indonesian positive law. Employing a descriptive qualitative methodology, data were collected through interviews, observations, and document analysis. The findings reveal that the practice is legally valid under Islamic law if the essential pillars and conditions of marriage are fulfilled, and may be classified as ʿurf ṣaḥīḥ when it does not contradict sharia principles. However, under Indonesian state law, the marriage holds no legal standing unless registered with the Office of Religious Affairs (KUA). In conclusion, this tradition reflects a form of legal and cultural syncretism between local customs, Islamic jurisprudence, and formal legal norms—requiring thoughtful management and contextual understanding.